Early Childhood Trajectories of Conduct Problems and Hyperactivity/Attention Problems: Predicting Adolescent and Adult Antisocial Behavior and Internalizing Problems. Issue 2 (3rd March 2020) - Galán, Chardée A.; Wang, Frances L.; Shaw, Daniel S.; Forbes, Erika E.
Abstract : Although conduct problems (CP) and hyperactivity/attention problems (HAP) are thought to covary with regularity, few studies have traced the probability of co-occurring CP and HAP longitudinally, particularly beginning in the toddler period. Further, there is little research examining how early co-occurring trajectories of CP and HAP predict functioning across several domains through late adolescence and early adulthood. Using a cohort of 284 low-income boys, we examined whether separate developmental trajectories of overt CP and HAP symptomatology from ages 2 to 10 relate to violent behavior, established correlates of antisocial behavior, impulsivity, and internalizing problems in adolescence and early adulthood. Co-occurring trajectory patterns of CP and HAP from ages 2 to 10 were also investigated in relation to later maladjustment. Findings indicated that trajectories of CP beginning in early childhood were related to violent behavior in adolescence and adulthood, adolescent correlates of antisocial behavior (i.e., deviant talk with peers), and internalizing problems in adulthood. Early HAP trajectories were also related to later problem behaviors when considered in isolation. However, when examining trajectories of CP and HAP simultaneously, children with chronic CP + chronic HAP, but not HAP-only, were most at risk for multiple types of problem behaviors in adolescence and early adulthood, including violent behavior and depressive and anxiety symptoms. Thus, HAP symptomatology was no longer predictive of adolescent and adult functioning once co-occurring CP was accounted for. Findings extend prior research with older children of HAP and/or CP, highlighting the predictive value of trajectories of CP beginning in the toddler period.